Weighted zero-sum problems over C₃ʳ - Godinho, H.; Lemos, A.; Marques, D. (Algebra and Discrete Mathematics, 2013)
Let Cn be the cyclic group of order n and set sA(Crn) as the smallest integer ℓ such that every sequence S in Cʳn of length at least ℓ has an A-zero-sum subsequence of length equal to exp(Cʳn), for A = {−1, 1}. In this paper, among other things, we give estimates for sA(C₃ʳ), and prove that sA(C₃³) = 9, sA(C₃⁴) = 21 and 41 ≤ sA(C₃⁵) ≤ 45.